Encouraging cycling in rural municipalities. - (:unkn) unknown (My University, 2013)
Compared to big cities, rural areas pose different and greater challenges when it comes to cycling promotion. The different stakeholders have different responsibilities and thus a large amount of coordination is needed. With car use being the dominant mode of transport, cycling levels are typically lower than in big bicycle-friendly cities. On the other hand, cycling tourism and cycling in combination with public transport offer great potential for the development of cycling. Providing safe cycle facilities in rural areas depends first and foremost on the planning of cycle paths along the main roads. It is essential to enable cyclists to cross the road safely given the high motor-vehicle speeds. Measures to reduce vehicle speeds are increasingly tested also on rural roads with low motor-vehicle flows, particularly in the Netherlands. (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Fahrradweg; Radverkehrsplanung; Radverkehrsanlage; Fahrradinfrastruktur; Regelwerk; Radweg; Schutzstreifen; Fahrradstreifen